Performance measures and worker productivity - Jan Sauermann (IZA World of Labor, 2023)
Measuring workers' productivity is important for public policy and private-sector decision-making. Due to the lack of a general measure that captures workers' productivity, firms often use one- or multi-dimensional performance measures, which can be used, for example, to analyze how different incentive systems affect workers' behavior. The public sector itself also uses measures to monitor and evaluate personnel, such as teachers. Policymakers and managers need to understand the advantages and disadvantages of the available metrics to select the right performance measures for their purpose.
Keywords: J24; M12; D24; 330; worker productivity; performance measures; human resource management